Lipase activation by molecular bioimprinting: The role of interactions between fatty acids and enzyme active site. (27th August 2020) - Brandão, Luma M. de S.; Barbosa, Milson S.; Souza, Ranyere L.; Pereira, Matheus M.; Lima, Álvaro S.; Soares, Cleide M. F.
Abstract: Bioimprinting is an easy, sustainable and low‐cost technique that promotes a printing of potential substrates on enzyme structure, inducing a more selective and stable conformation. Bioimprinting promotes conformational changes in enzymes, resulting in better catalytic performance. In this work, the effect of bioimprinting of Burkholderia cepacia lipase (BCL) and porcine pancreatic extracts (PPE) with four different fatty acids (lauric acid (C12:0), myristic acid (C14:0), palmitic acid (C16:0), and stearic acid (C18:0)) was investigated. The results demonstrated that the better bioimprinting effect was in BCL with lauric acid in esterification reaction, promoting BCL activation in which relative enzyme activity was 70 times greater than nonimprinted BCL. Bioimprinting results were influenced by the carbon chain length of fatty acids imprinted in the BCL, in which the effects were weaker with the chain increase. Molecular docking was performed to better understand the bioimprinting method. The results of these simulations showed that indeed all fatty acids were imprinted in the active site of BCL. However, lauric acid presented the highest imprinting preference in the active site of BCL, resulting in the highest relative activity. Furthermore, Fourier transform infrared (FTIR) analysis confirmed important variations in secondary structure of bioimprinting BCL with lauric acid, in which there was a reduction in the α‐helix content and an increase in the β‐sheet content that facilitated substrate access to the active site of BCL and led higher rigidity, resulting in high activity. Bioimprinted BCL with lauric acid showed excellent operational stability in esterification reaction, maintaining its original relative activity after five successive cycles. Thus, the results show that bioimprinting of BCL with lauric acid is a successful strategy due to its high catalytic activity and reusability.